Selective enrichment of newly synthesized proteins for quantitative secretome analysis - Eichelbaum, Katrin; Krijgsveld, Jeroen (Nature biotechnology, 2012)
Secreted proteins constitute a large and biologically important subset of proteins that are involved in cellular communication, adhesion and migration. Yet secretomes are understudied because of technical limitations in the detection of low-abundance proteins against a background of serum-containing media. Here we introduce a method that combines click chemistry and pulsed stable isotope labeling with amino acids in cell culture to selectively enrich and quantify secreted proteins. The combination of these two labeling approaches allows cells to be studied irrespective of the complexity of the background proteins. We provide an in-depth and differential secretome analysis of various cell lines and primary cells, quantifying secreted factors, including cytokines, chemokines and growth factors. In addition, we reveal that serum starvation has a marked effect on secretome composition. We also analyze the kinetics of protein secretion by macrophages in response to lipopolysaccharides.